Which Acute Ischemic Stroke Patients Are Fast Progressors?: Results From the ESCAPE Trial Control Arm. Issue 5 (5th April 2021) - Ospel, Johanna M.; Hill, Michael D.; Kappelhof, Manon; Demchuk, Andrew M.; Menon, Bijoy K.; Mayank, Arnuv; Dowlatshahi, Dar; Frei, Don; Rempel, Jeremy L.; Baxter, Blaise; Goyal, Mayank
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: Fast infarct progression in acute ischemic stroke has a severe impact on patient prognosis and benefit of endovascular thrombectomy. In this post hoc analysis of the ESCAPE trial (Endovascular Treatment for Small Core and Proximal Occlusion Ischemic Stroke), we identified acute ischemic stroke patients with rapid infarct growth and investigated their baseline clinical and imaging characteristics. Methods: Control arm patients were included if they had follow-up imaging at 2-8 hours without substantial recanalization, and if their baseline Alberta Stroke Program Early CT Score was ≥9. Fast infarct progression was defined as Alberta Stroke Program Early CT Score decay ≥3 points from baseline to 2- to 8-hour follow-up imaging. Clinical and imaging baseline characteristics were compared between fast progressors and other patients, and occlusion site and collateral flow patterns were assessed in detail. Results: Fast infarct progression occurred in 15 of 43 included patients (34.9%). Fast progressors had worse collaterals (poor in 3/15 [20%] versus 0/28 patients, P =0.021) and more carotid-T or -L occlusions (8/15 [53.4%] versus 3/28[10.7%], P =0.021). In 8 out of 15 (53.3%), occlusion site and circle of Willis configuration prevented collateral flow via the anterior or posterior cerebral artery. Conclusions: Most patients with fast infarct progression had terminal carotid occlusions and impaired collateral flow via the anterior or posterior cerebral artery, indicating that occlusion location and intracranial vascular anatomy are relevant for infarct progression.